Clinical Features and Pathophysiology of Disorders of Arousal in Adults: A Window Into the Sleeping Brain - Baldini, Tommaso; Loddo, Giuseppe; Sessagesimi, Elisa; Mignani, Francesco; Cirignotta, Fabio; Mondini, Susanna; Licchetta, Laura; Bisulli, Francesca; Tinuper, Paolo; Provini, Federica (Frontiers in Neurology, 2019)
Introduction: Disorders of Arousal (DoA) are NREM parasomnias that have been typically regarded as self-limited childhood manifestations. It is now clear that DoA can persist in adults, often presenting with distinctive characteristics. So far, few studies have described the clinical course and characteristics of DoA in adulthood, therefore a large part of their semiology is ignored. The aim of this study is to describe the clinical manifestations of DoA in an adult population and to provide a pathophysiological interpretation of their features. Methods: We screened our database for all 1,600 adult ( 15 years) patients with sleep-related motor behaviors between 1995-2016. We identified 45 patients with typical DoA episodes, of whom a complete history, neurological examination and diagnostic video-polysomnography (VPSG) were available. All the patients provided a detailed description of their episodes (with particular regards to semiology, frequency and association with stressful life events) in different life periods. VPSG recordings were reviewed and DoA episodes were identified and assigned to three different categories according to their complexity. Results: Our population was composed of 45 adult patients ranging between 15-76 years. Sleepwalking was reported by 86% of patients, possibly associated with complex interactions with the environment and violent behaviors in 53% of cases; distressing mental contents were reported by 64 %. Recall of the episodes was reported in 77% of patients. Non-restorative sleep was reported in 46% of patients. Stress was a potential episode trigger in 80% of patients. VPSG recordings documented 334 DoA episodes. According to our classification of motor patterns, 282 episodes (84%) were Simple Arousal Movements (SAMs), 34 (10%) Rapid Arousal Movements (RAMs) and 18 (5%) Complex Arousal Movements (CAMs). Discussion: Our study confirms that DoA in adulthood present with distinctive characteristics, such as non-restorative sleep, violence and complex or bizarre behaviors. Alternative classifications of DoA based on motor patterns could be useful to characterize DoA episodes in adults, as different motor patterns often coexist in the same individual and minor episodes are more common but generally underreported by patients. Prospective studies are needed for a definitive characterization of DoA in adulthood throughout the life course.